Response to Letter: Upper eyelid platinum weight placement for the treatment of paralytic lagophthalmos: A new plane between the inner septum and the levator aponeurosis - Oh, Tae Suk; Min, Kyunghyun; Song, Sin Young; Choi, Jong Woo; Koh, Kyung Suk (Archives of plastic surgery, 2018)
KCI Citation Count: 0